Análisis de potencial eólico y selección de aerogenerador. Caso de estudio Universidad Antonio Nariño sede Buganviles-Neiva (2023)
Colombia is committed to energy transition and environmental sustainability. Universities are an important source of high energy consumption, especially in the city of Neiva, where ambient temperatures exceed the average values of other cities in the country. The UAN Buganviles campus has an average annual energy consumption of 2429 kW, due to the need to constantly use refrigeration and lighting equipment in the different areas to carry out academic and administrative activities. Currently, studies on wind speed in Neiva are limited, and the wind speed and wind potential to supply these energy demands are unknown. The research carried out seeks to analyze the wind potential for a possible selection of a wind turbine for the Antonio Nariño University, Buganviles-Neiva campus. The methodology employed comprises 3 phases: wind potential estimation, wind rose analysis and wind potential analysis, using the Weibull distribution. The results indicated that a 70PRO generator covers 5% of the consumption demand of the UAN, which represents a saving of $8,056,881 million COP/year; it is concluded that with 10 70PRO wind turbines it is possible to cover 50% of the demand of the Antonio Nariño University in 2022; The payback period for the investment if the entire project is implemented is 6 years.